Cities of noise: a brief inquiry into sensemaking, sensemakers and organized worlds - Patriotta, Gerardo (Academy of Management, 2015)
In his novel The Unbearable Lightness of Being, Czech author Milan Kundera suggests that a novel is “an investigation of human life in the trap the world has become”. Novels are, indeed, arguably the most subtle tool of ontological inquiry, insightful meditations on how individuals, faced with questions and enigmas related to human existence, make sense of their ‘being in the world.’ (Heidegger, 1962). I have always admired the mastery with which great novelists are able to dissect and convey the most intricate aspects of human situations through their characters and plots. Novelists’ investigations are typically triggered by twists and turns that generate disturbance in the status quo and call for interpretations on the part of the characters involved. I refer to this disturbance as ‘noise’. In this essay, I shall comment on a tale of three cities that share the attribute of noise and are depicted in literary works by Milan Kundera, Robert Musil and Italo Calvino. I shall use this tale to develop considerations that are relevant to the world of organizations, and I shall also highlight some ways in which organizational scholars can learn from novelists.